Employee Relations, Tacit Knowledge Sharing Activities, And Employee Performance in Social Exchange Theory Perspective - Ari Pradhanawati; Reni Shinta Dewi; Chusnu Syarifa Diah Kusuma (JURNAL ILMU SOSIAL, 2022)
Modern-day enterprise competition is getting more difficult, in particular in the industry 4.0 generation. SMEs or Small and medium-sized corporations as a part of the pillar in the economic industries, want to assume these conditions. Batik is an SME that has contributed to the economic system. various issues are confronted by way of the batik enterprise, together with SMEs in Batik in Semarang. They face a few barriers, inclusive of increasing the capability of human resources. knowledge sharing is an activity to enhance individual talents, specifically trouble-solving and worker self-assurance. Knowledge sharing is an activity to improve individual skills, especially problem-solving and employee confidence. The purpose of this examination turned into exploring the effect on tacit knowledge-sharing activities, employee performance and employee relations. Also, the article defined the activity of tacit knowledge sharing in mediating the effect of employees relation and employee performance. The type of research was explanatory research. The sample was a hundred employees within the SMEs Batik in Semarang. Statistics evaluation of the use of SEM. The finding showed that there was an effect of employee relations on tacit knowledge-sharing activities. Second, there was an effect of tacit knowledge-sharing activities on employee performance. And, employee relations and employee performance had a positive effect. The results of the mediation effect test showed that employee relations have a positive effect on employee performance through tacit knowledge-sharing activities. The suggestion of this research is Batik UKM in Semarang to create a conducive work environment because the results of the study show that the relationship between employees is a success factor in sharing tacit knowledge. The limitation of this research is that the study was only conducted at the Batik UKM in Semarang, which resulted in a very limited generalization of the research findings. The limitation of this research is that the study turned into best carried out on the Batik UKM in Semarang, which led to a totally limited generalization of the research findings. The difficulty of the have a look is that the observation turned into only carried out at the SMEs Batik in Semarang which makes a completely constrained generalization of the findings.